Intimate citizenship and the tightening of migration controls in the United Kingdom. (21st August 2019) - Nehring, Daniel; Sealey, Clive
Abstract: This article examines recent changes in British family migration policy. It explores the reasons for these policy changes. It highlights the fact that these changes have affected the legal, financial, social, and lived experiences of transnational couples. It uses primary research to exemplify these changes. For example, it highlights the fact that the changes in policy have had some negative impacts on the ability of transnational families to have intimate relationships with each other. Some of these changes have led to the separation of couples. Other changes have led to what couples outline as an involuntary separation from the United Kingdom. This research has current and future relevance in the context of the focus of the current government and the likelihood that policy will be tightened even further in the aftermath of Britain leaving the EU, post‐Brexit.